Extracorporeal shock wave therapy in periodontics: A new paradigm - Munivenkatappa Lakshmaiah Venkatesh Prabhuji; Shaeesta Khaleelahmed; Sujatha Vasudevalu; K. Vinodhini (Wolters Kluwer Medknow Publications, 2014)
The quest for exploring new frontiers in the field of medical science for efficient and improved treatment modalities has always been on a rise. Extracorporeal shock wave therapy (ESWT) has been enormously used in medical practice, principally, for the management of urolithiasis, cholelithiasis and also in various orthopedic and musculoskeletal disorders. The efficacy of ESWT in the stimulation of osteoblasts, fibroblasts, induction of neovascularization and increased expression of bone morphogenic proteins has been well documented in the literature. However, dentistry is no exception to this trend. The present article enlightens the various applications of ESWT in the field of dentistry and explores its prospective applications in the field of periodontics, and the possibility of incorporating the beneficial properties of shock waves in improving the treatment outcome.